Penggunaan teknologi AI dalam pengembangan bahasa Inggris - Nurhayati, Dwi (Maliki Interdisciplinary Journal, 2024)
This article aims to describe the use of Artificial Intelligence (AI) technology in the development of the English language. The method used in this research is a Systematic Literature Review. The research results show that the use of Artificial Intelligence (AI) in the development of English has become a trend in learning and teaching, especially in this modern era. Artificial Intelligence (AI) plays many roles in life, especially in education, as it opens up many access points for ease in enhancing knowledge, particularly in the development of English.